SOSIALISASI SMART CAMPUS FAKULTAS PERTANIAN UNIBA SURAKARTA DI DINAS PERTANIAN DAN PERIKANAN KABUPATEN SUKOHARJO - Pramono Hadi; Libria Widiastuti; Irma Wardani; Bagus Andika Fitroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The implementation of community service has been carried out at the Agriculture and Fisheries Service of Sukoharjo Regency. Those present at the event were the Dean of the Faculty of Agriculture, Head of Agrotechnology Study Program, Head of Agribusiness Study Program and Head of Animal Husbandry Study Program of UNIBA Surakarta. Meanwhile, from the Service, the representative of the Head of the Agriculture and Fisheries Service was present. The extension workers who attended were 17 agricultural extension workers. The community service method used was FGD (Focus Group Discussion). Guided by a moderator with the aim of initiating and exploring the objectives to be achieved. The results of this service are very encouraging that as the representative of the service, they are very enthusiastic to participate and will send their extension workers to training in the use of IoT and IA-based technology held by UNIBA Solo and mentoring is carried out until the extension workers are proficient in using it.